Implementation of Deep Learning CNN Algorithm for Classification of Gas Station Digitization Inventory Devices - Doli Sawaluddin; Zuhri Ramadhan (Journal of Information Technology, computer science and Electrical Engineering, 2025)
The process of digitizing gas station devices requires careful data validation, especially on device images that are often subject to input errors. To overcome this, this research proposes the use of Convolutional Neural Network (CNN) algorithm with transfer learning technique. The pre-trained CNN model will be used to classify the device images into 13 classes. For the sake of development flexibility, the data is divided into 2 separate models.